A2.03 The PD-1/PD-L1 axis is modulated by pro-inflammatory cytokines. (24th February 2016) - Bommarito, D; Hall, C; Taams, LS; Corrigall, VM
Abstract : Background: The Programmed Cell Death 1 (PD-1) receptor plays a major role in maintaining self-tolerance. Engagement of PD-1 with its ligand PD-L1 on CD4 + T cells is reported to downregulate inflammatory responses through inhibition of cell proliferation and cytokine production. In inflammatory arthritis (IA), PD-1 is described as overexpressed on synovial fluid (SF) CD4 + T cells compared to peripheral blood (PB) CD4 + T cells while conflicting evidence exists regarding the expression and functionality of PD-L1 during chronic inflammation. The aim of this study was to determine (i) PD-1 and PD-L1 expression on IA SF CD4 + T cells and (ii) the effects of the pro-inflammatory cytokines TNFα and IL-6 on PD-1 ligation in healthy control (HC) CD4 + T cells. Materials and methods: CD4 + T cells were isolated from PB of HC or patients with IA and cultured in anti-CD3 or anti-CD3/PD-L1fc chimaera coated plates. IL-6 (10 ng/ml) +/- anti-IL-6R (tocilizumab; 1 ug/ml), or TNFα (10 ng/ml) or acellular SF (0.5%) +/- anti-TNFα (adalimumab; 1ug/ml) were added to the cultures. Proliferation was assessed at day 5 by 3 H-thymidine uptake. Day 5 supernatants were analysed by ELISA for soluble PD-1 (sPD-1). Results: IA SF samples were enriched for PD-1+CD4 + T cells compared to PB (n = 6, p = 0.03) while no significant difference was observed in the percentage of PD-L1+ T cells. CD4 + T cells from HC showed a significant decrease in proliferation upon PD-1 ligation (n = 8; p < 0.05) while CD4 + T cells from IA patients appeared more resistant (n = 8; p > 0.05). In HC CD4 + T cell cultures, addition of TNFα or IL-6 completely abrogated PD-L1fc activity (n = 10; p > 0.05). In these cultures, the TNFα and IL-6 effect was neutralised by adalimumab (n = 9) and tocilizumab (n = 6) (p < 0.05). Addition of a-cellular SF (0.5%) to HC CD4 + cell cultures (n = 3) also reduced the effects of PD-1 crosslinking. ELISA analysis showed that both TNFα or IL-6 induced sPD-1 production (n = 7; p < 0.05) and that adalimumab and tocilizumab successfully blocked this effect. Conclusion: We hypothesise that the pro-inflammatory cytokines TNFα and IL-6 modulate CD4 + T cells reactivity to PD-L1 by inducing the release of a soluble form of PD-1 which might interfere with PD-1/PD-L1 signalling.